1997
DOI: 10.1021/ie960668f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Vegetable Oils in Sub- and Supercritical Water

Abstract: Water, in its subcritical state, can be used as both a solvent and reactant for the hydrolysis of triglycerides. In this study, soybean, linseed, and coconut oils were successfully and reproducibly hydrolyzed to free fatty acids with water at a density of 0.7 g/mL and temperatures of 260−280 °C. Under these conditions the reaction proceeds quickly, with conversion of greater than 97% after 15−20 min. Some geometric isomerization of the linolenic acids was observed at reaction temperatures as low as 250 °C. Rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(118 citation statements)
references
References 17 publications
5
102
1
1
Order By: Relevance
“…1,5 It was verified that to low temperatures, the speed and the yield of the hydrolysis reaction are both practically null. Figure 1 and Table 1 illustrates a typical profile of triglycerides (TG) obtained of non hydrolyzed corn oil, while Figures 2 to 3 illustrate the variation of the chromatographic profile of a hydrolyzed corn oil as a function of the temperature.…”
Section: Hydrolysis Of the Corn Oilmentioning
confidence: 99%
See 2 more Smart Citations
“…1,5 It was verified that to low temperatures, the speed and the yield of the hydrolysis reaction are both practically null. Figure 1 and Table 1 illustrates a typical profile of triglycerides (TG) obtained of non hydrolyzed corn oil, while Figures 2 to 3 illustrate the variation of the chromatographic profile of a hydrolyzed corn oil as a function of the temperature.…”
Section: Hydrolysis Of the Corn Oilmentioning
confidence: 99%
“…17, No. 1,2006 (ammonium chlorite, methanol, sulfuric acid) are added and the contents of the capped tube heated in water bath (temperature 90 °C) for 10 min, being after words cooled in ice bath and later added 5 mL of hexane and 10 mL of water. A sample is taken from the clear upper layer (usually 1 μL) for GC analysis of FAMEs.…”
Section: Fame Analysis By Hrgc/msmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the main compositions of the glycerol degradation were methanol, ethanol, acrolein, allyl alcohol, formaldehyde, propionaldehyde, acetaldehyde and gas products. In terms of fatty acids, they have high stability in subcritical water [40][41][42]. The production of fatty acids with higher molecular weight via hydrolysis of lipids may be favored in subcritical water without alkaline conditions.…”
Section: Lipidsmentioning
confidence: 99%
“…A água em estado supercrítico apresentou bons resultados, além de ser considerada uma rota limpa, pois não utiliza solvente nem catalisadores que podem ser nocivos ao meio ambiente. 44,45 Foi ainda reportado o uso de CO 2 supercrítico como solvente, sendo observado que este possui as mesmas vantagens da água supercrítica e ainda facilita o processo de separação dos ácidos graxos dos outros produtos. 46 …”
Section: Figura 1 Reação De Transesterificação Ou Alcoólise De Triacunclassified